Personalized extended interval dosing of natalizumab in MS: A prospective multicenter trial. (11th August 2020) - van Kempen, Zoé L.E.; Hoogervorst, Erwin L.J.; Wattjes, Mike P.; Kalkers, Nynke F.; Mostert, Jop P.; Lissenberg-Witte, Birgit I.; de Vries, Annick; ten Brinke, Anja; van Oosten, Bob W.; Barkhof, Frederik; Teunissen, Charlotte E.; Uitdehaag, Bernard M.J.; et al.
Abstract : Objective: To determine whether natalizumab efficacy is maintained when switching to personalized extended interval dosing based on individual natalizumab trough concentrations in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: This was a prospective multicenter single-arm trial with 1 year follow-up and a 1-year extension phase. Participants were adult persons with RRMS treated with natalizumab without disease activity in the year prior to enrollment. The natalizumab treatment interval was based on longitudinal natalizumab trough concentrations. Patients received 3 monthly MRI scans, relapse assessments, and disability scoring during follow-up. The primary endpoint was the occurrence of gadolinium-enhancing lesions on MRI. Secondary endpoints were new/enlarging T2 lesions on MRI and relapses and progression on the Expanded Disability Status Scale (EDSS) during follow-up and extension phase. Results: Sixty-one patients were included. Eighty-four percent extended the interval from a 4-week interval to a 5- to 7-week interval. No patient developed gadolinium-enhancing lesions (95% confidence interval [CI] 0%–7.4%) during follow-up. No new/enlarging T2 lesions (95% CI 0%–7.4%) or relapses (95% CI 0%–7.4%) were reported during follow-up and in the extension phase. Median EDSS was comparable at baseline (3.0, interquartile range [IQR] 2.0–5.0) and after follow-up (3.0, IQR 2.0–5.0). Conclusion: Personalized extended interval dosing did not induce recurrence of MS disease activity. Natalizumab efficacy was maintained in stable patients with RRMS receiving personalized extended interval dosing based on individual natalizumab concentrations. Classification of evidence: This study provides Class IV evidence that personalized extended interval dosing of natalizumab does not result in recurrence of disease activity in stable patients with RRMS.